Effects of a lifestyle development program designed to reduce the risk factors for cognitive decline on the mental health of elderly individuals. Issue 4 (26th February 2020) - Takeda, Shinya; Fukushima, Haruhiko; Okamoto, Chihiro; Kitawaki, Yasushi; Nakayama, Shigeki
Abstract : Background: The incidence of Alzheimer's disease (AD) along with depression is high in the elderly. In the present study, a program that allows the elderly individuals to voluntarily manage and develop lifestyles that may reduce the risk factors for cognitive decline was applied to the participants to evaluate its effect on the mental health of these individuals. Methods: The participants were randomly assigned to an intervention group and a control group. The program was conducted during 7 months in the intervention group, and it had seven times of group activities, performed once a month for about 1 h, and individual activities to reduce the risk factors for cognitive decline, performed every day. To evaluate the effects of the program on the mental health of the participants, the Geriatric Depression Scale (GDS) and Philadelphia Geriatric Center Morale Scale (PGC) were used. These two scales were applied twice to the intervention and control groups. Results: The GDS score revealed no change in the score in the intervention group before and after the 7‐month program implementation; however, in the control group, the score was significantly higher after program implementation than that before. The PGC score revealed no change in the intervention group before and after 7‐month program implementation; however, in the control group, the score was significantly lower after program implementation than that before. Additionally, it revealed no change in the GDS score in the depression‐prone control group before and after 7‐month program implementation; however, in the depression‐prone intervention group, the GDS score was significantly lower after program implementation than that before. Conclusions: The intervention program that allows the elderly individuals to voluntarily manage and develop lifestyles that may reduce the risk factors for cognitive decline is expected to maintain mental health in elderly individuals.